Enhancing knowledge articulation in communities of practices: the role of the community leader. (2018) - Haagensen, Isabell Schonhowd; Helland, Eline Katrin; Nesheim, Torstein
In recent studies, it is argued that communities of practice (CoP) should be supported by management and backed by formal, organisational mechanisms. In this paper, tools that are initiated and used by the coordinators/leaders of CoP are studied. Based on a study of formal networks in a large organisation, four measures intended to enhance knowledge articulation are identified and analysed; the use of a core group as a structural tool, improvement of meetings, implementation of ICT-tools and engagement of network members who have their primary obligations elsewhere in the organisation. A number of implications for further research are drawn.